Prenatal Lipopolysaccharides Exposure Induces Transgenerational Inheritance of Hypertension. Issue 14 (25th August 2022) - Cao, Nian; Lan, Cong; Chen, Caiyu; Xu, Zaicheng; Luo, Hao; Zheng, Shuo; Gong, Xue; Ren, Hongmei; Li, Zhuxin; Qu, Shuang; Yu, Cheng; Yang, Jining; et al.
Abstract : Background: Adverse environmental exposure during the prenatal period can lead to diseases in the offspring, including hypertension. Whether or not the hypertensive phenotype can be transgenerationally transmitted is not known. Methods: Pregnant Sprague Dawley rats were intraperitoneally injected with lipopolysaccharide (LPS) on gestation days 6, 8, 10, and 12 to generate the prenatal LPS exposure model. Blood pressure was monitored by both telemetry and tail-cuff method. RNA sequencing was performed to analyze transcriptome alteration in the kidney of the third generation. Tempol and spironolactone were used to test the potential preventative and therapeutic effect of targeting reactive oxygen species and mineralocorticoid receptor signaling, respectively. Molecular biological experiments were performed to illustrate the mechanism of epigenetic and transcription regulation. Results: Prenatal LPS exposure can impair the ability to excrete a salt load and induce hypertension from the first to the third generations, with the fourth and fifth generations, inducing salt-sensitive hypertension. Compared with control pups, the transcriptome in the kidney of the hypertensive third-generation prenatal LPS–exposed offspring have upregulation of the Ras-related C3 botulinum toxin substrate 1 ( Rac1 ) gene and activation of mineralocorticoid receptor signaling. Furthermore, we found that LPS exposure during pregnancy triggered oxidative stress that upregulated KDM3B (histone lysine demethylase 3B) in the oocytes of first-generation female rats, leading to an inheritable low level of H3K9me2 (histone H3 lysine 9 dimethylation), resulting in the transgenerational upregulation of Rac1 . Based on these findings, we treated the LPS-exposed pregnant rats with the reactive oxygen species scavenger, tempol, which successfully prevented hypertension in the first-generation offspring and the transgenerational inheritance of hypertension. Conclusions: These findings show that adverse prenatal exposure induces transgenerational hypertension through an epigenetic-regulated mechanism and identify potentially preventive and therapeutic strategies for hypertension.